Evaluation of efficiency and contamination rates of different controlled pollination methods in Eucalyptus - Valencise Bonine, Cesar Augusto; Perantoni Fuchs, Maria Cecilia [UNESP]; Marino, Celso Luis [UNESP] (Ipef-inst Pesquisas Estudos Florestais, 2015)
Eucalypts are widely used to produce various kinds of products. Controlled pollination methods used in breeding programs can produce desirable characteristics, such as growth and productivity, in the first generation. Considering the continuing need for cost reduction and improved efficiency, research on the various controlled pollination techniques is needed. The objective of this study was to compare four different techniques of controlled pollination (conventional; one-stop pollination - OSP; OSP with pollen saturation - OSPPS; and OSP with insecticide - OSPI) in terms of pollen contamination, percentage of capsule retention, and operational performance. Capsule retention and operational performance were analyzed statistically and contamination analyses were performed using microsatellite markers. All tested pollination methods proved efficient in avoiding contamination. The conventional controlled pollination and the OSPPS had the highest percentage of capsule retention. The OSPPS and OSPI methods obtained better results for operational performance compared to conventional controlled pollination and OSP. Based on our results, the OSPPS method is recommended because it produced the best results for all evaluated parameters.
Keywords: Controlled pollination; pollen contamination; microsatelites markers; operational performance